2020
DOI: 10.3390/toxics8010011
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Trace Elements in Subjects Living Near a Hazardous Waste Incinerator: Concentrations in Autopsy Tissues

Abstract: The only hazardous waste incinerator (HWI) in Spain started to operate in 1999. Twenty years later, the levels of 11 trace elements (As, Be, Cd, Cr, Hg, Mn, Ni, Pb, Sn, Tl and V) were analyzed in five different autopsy tissues (kidney, liver, brain, bone and lung) from 20 individuals who had been living near the facility. In 2019, As, Be, Tl and V were not detected in any of the analyzed tissues, while Hg could be only quantified in very few samples. The highest levels of Cd and Pb were found in kidney and bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…Therefore, dietary exposure would be greater than 99% of the total exposure. In agreement to data from the scientific literature [ 42 , 43 ], these estimations clearly indicate that food consumption is the most contributing factor to the total health risks derived from the exposure to PCDD/Fs and PCBs.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, dietary exposure would be greater than 99% of the total exposure. In agreement to data from the scientific literature [ 42 , 43 ], these estimations clearly indicate that food consumption is the most contributing factor to the total health risks derived from the exposure to PCDD/Fs and PCBs.…”
Section: Discussionsupporting
confidence: 88%
“…Pb concentration data in human tissues from this study are comparable to the study of Mari et al [ 21 ], who reported that the concentration of Pb in the kidney was 0.18 μ g/g. Recently, García et al [ 28 ] have estimated the concentration of Pb in human tissues (liver, kidney, brain, lung, and bone) with a range of 0.08 to 1.0 μ g/g. In the next step, we attempted to find the correlation between Ca and Cd or Pb concentrations in the TCL.…”
Section: Discussionmentioning
confidence: 99%
“…Pb concentration data in human tissue from this study are comparable to Mari et al [16] , who reported that the concentration of Pb in the kidney was 0.18 μg/g. Recently, García et al [17] have estimated the concentration of Pb in human tissues (liver, kidney, brain, lung, and bone) with a range of 0.08 to 1.0 μg/g. In the next step, we attempted to fi nd the correlation between Ca and Cd or Pb concentrations in the TCL.…”
Section: Figure 1: Icp-ms Analyses Were Performed On Samples From the Tcls Of 40 Patients With Cts (A) The Concentration Of Ca (B) Concenmentioning
confidence: 99%